Cultural Values and Overall Fairness; - Mohsen Golparvar; Mohammadali Nadi (Taḥqīqāt-i Farhangī-i Īrān)
This research conducted with the aim of investigating the relationships between overall fairness and cultural values with organizational justice, job satisfaction and turnover among the personnel of training and education administrations in Esfahan city. Statistical population were the personnel of education and training administrations regions, which 309 persons from them selected with using simple random sampling. Research instruments were overall fairness with 3 items, cultural values (in two fields including materialism and power distance with 8 items), distributive, procedural and interactional justice with 3,3,3 items respectively, job satisfaction with 3 items and turnover with 3 items. Data were analyzed with using Pearson’s correlation coefficient, structural equation modeling, moderated hierarchical regression and mediating regression analysis. Results showed that there are significant relations between overall fairness with distributive, procedural, interactional justice and turnover, job satisfaction and materialism (P<0.01) but there is not significant relation between power distance with overall fairness (P>0.05). The results of structural equation modeling and mediating regression analysis showed that overall fairness relatively mediate the relations between procedural justices with turnover. But there was not mediated role for overall fairness in relations between distributive and interactional fairness with turnover and job satisfaction. Moderated regression analysis showed that power distance likely have moderated role in relations between overall fairness with turnover likely.